Recyclability of CsPbBr3 quantum dot glass nanocomposites for their long-standing use in white LEDs - Vahedigharehchopogh, Naji; Erol, Erdinc; Kibrisli, Orhan; Genc, Aziz; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2022)
The embedding of CsPbBr3 perovskite quantum dots (PQDs) in an inorganic glass matrix not only protects them against chemical, thermal, and photodegradation but also provides an effective strategy to isolate toxic elements such as Pb from the environment for a long period of time. Herein, the recyclability of glass is another important feature that contributes to environmental sustainability. Hence, effective and efficient recycling technologies are needed for the widespread use of PQD glass nanocomposites (GNCs) in many commercial applications. However, studies on the recyclability of CsPbBr3 PQD GNCs have not been conducted so far. Therefore, in this work, we investigate the structural, thermal, optical, and photoluminescence properties of recycled CsPbBr3 PQD GNCs to assess their suitability as long-standing and reusable luminescent materials. For this purpose, the recyclability of GNCs is checked by three repeated melt-quenching and subsequent heat-treatment processes. Although the color emission properties of GNCs under the same heat-treatment conditions show a slight variation after each recycling step, PQD GNCs almost retain their PLQY even after the last recycling step. Ultimately, a prototype white light-emitting diode is constructed by coupling recycled PQD GNCs and a commercial red phosphor on top of a blue LED chip showing high-performance with CIE color coordinates of x = 0.3228, y = 0.3470 and a CCT value of 5920 K. The findings of this work reveal that the recyclability of PQD GNCs holds great promise for a more sustainable technology.
Keywords: OPTICAL-PROPERTIES; PEROVSKITE; STABILITY; EFFICIENT; RECOVERY; PROGRESS; LASERS; Materials Science; Physics